The research of the operating mode of the concrete mixture plane depth compactor with a circular vibration exciter - Maslov, Alexander; Batsaikhan, Janar (Academic journal Industrial Machine Building Civil Engineering, 2019)
The paper proposes an essentially new design of a concrete mixture depth compactor made in the form of a vertical plate witha circular vibration exciter mounted on its upper part. A design diagram of the «plane depth compactor – concrete mixture»dynamic system is presented and the vertical plate movement equations describing its linear vibrations in the horizontal planeand torsional vibrations in relation to the center of gravity are provided. It has been determined the regularity of the verticalplate motion during the compaction of concrete mixtures. The provided results of the research enable the substantiation of therational parameters of the plane depth compactor performing spatial vibrations and the efficient modes of the vibratory actionon the concrete mixtures of different consistence.
Keywords: plane depth compactor; concrete mixture; vibration compaction